2024
DOI: 10.1039/d3ra07103k
|View full text |Cite
|
Sign up to set email alerts
|

Photonic post-processing of a multi-material transparent conductive electrode architecture for optoelectronic device integration

Luis Felipe Gerlein,
Jaime Alberto Benavides-Guerrero,
Sylvain G. Cloutier

Abstract: Photonic postprocess of multimaterial, highly conductive transparent electrodes. Separate annealing of AgNWs and crystallization of a TiO2 layer atop are proved. This novelty processing results in two opposing types of materials: nanowires and titania being transformed atop a PET substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The AgNWs were photonic cured with 9 pulses at a fluence per pulse of 1.15 J cm −2 resulting in a processing time of 4.7 s. The TiO 2 films were photonic cured with 3 pulses at a fluence per pulse of 6 or 7 J cm −2 resulting in a processing time of 20 s. They found that the TiO 2 film could be crystallized into either anatase or rutile phases by adjusting the pulse fluence between 6 and 7 J cm −2 , respectively. Their final transparent conductor films had a transmittance at 550 nm of 84% with a haze value of 7.7% and a sheet resistance of 18 Ω sq −1 [31]. Junghähnel et al applied photonic curing as a postdeposition method to annealed ITO and IZO films deposited at room temperature on flexible Willow Glass ® (WG) substrates.…”
Section: Transparent Conductorsmentioning
confidence: 99%
“…The AgNWs were photonic cured with 9 pulses at a fluence per pulse of 1.15 J cm −2 resulting in a processing time of 4.7 s. The TiO 2 films were photonic cured with 3 pulses at a fluence per pulse of 6 or 7 J cm −2 resulting in a processing time of 20 s. They found that the TiO 2 film could be crystallized into either anatase or rutile phases by adjusting the pulse fluence between 6 and 7 J cm −2 , respectively. Their final transparent conductor films had a transmittance at 550 nm of 84% with a haze value of 7.7% and a sheet resistance of 18 Ω sq −1 [31]. Junghähnel et al applied photonic curing as a postdeposition method to annealed ITO and IZO films deposited at room temperature on flexible Willow Glass ® (WG) substrates.…”
Section: Transparent Conductorsmentioning
confidence: 99%